Transference and Transparency: Digital Technology and the Remediation of Cinema - Bolter, Jay (Intermédialités / Intermediality, 2005)
New digital forms, particularly computer and video games pose a challenge to the cultural status that film has enjoyed for decades. This challenge provoked an anxiety about new media reflected in a series of films in the 1990s, including eXistenZ and The Matrix. Hollywood filmmakers have responded to the challenge with a two fold strategy: they have adopted computer-graphic special effects, while maintaining a commitment to linear narrative and transparent representation. Recently, the DVD has led the film industry to explore hybrid forms of representation and even interactivity.